PS-098 Reorganisation of medication circuit in the operating and delivery room. (25th February 2017) - Petit, C; Atkinson, S; Dubois, S; Crochetière, C; Bussières, JF
Abstract : Background: Pharmacy practice is highly regulated and the medication circuit is complex in healthcare settings. Required organisational practices of the national accreditation authority also provide a normative framework. Purpose: To describe the reorganisation of the medication circuit in the operating (OR) and delivery (DR) room. Material and methods: A prospective descriptive study was conducted in OR and DR in a 500 bed teaching hospital. Following a review of literature, an Ishikawa diagram was developed to identify failure modes. Thereafter, a semi-structured direct observation in OR and DR was done to identify key issues. Corrective measures were discussed and adopted by consensus with a multidisciplinary group, including pharmacists, anaesthesiologists, nurses and respiratory therapists. Results: 10 failure modes associated with the medication circuit and 18 key issues were identified. A total of 30 corrective measures were proposed. While all inpatient care areas have designated pharmacists to provide decentralised pharmaceutical care in the hospital, the OR and DR have none. Pharmacists were identified to share such coverage within their current intensive care and surgical care daily duties. Automated dispensing cabinets were implemented to better control drug dispensing and stock replenishing for each room. A safe anaesthesia box system was chosen and the drug content standardised with a detailed record sheet, improving the management and the documentation of prepared and administered doses, including residual quantities at the end of a shift. The system was pre-tested and improved before implementation. A radio-identification based system was also developed to manage RFID labels and anaesthesia box replenishing steps within the central pharmacy. A monitoring system was chosen to monitor cold chain of drugs stored in refrigerators. Expiration dates were reviewed according to current standards to minimise risks of contamination. Drug utilisation reviews were identified for drug targets to offer feedback to drug prescribers. Conclusion: OR and DR are often less supported by pharmacy to insure an optimal medication circuit. With a view to ensuring continuous improvement of quality of patient care, audits should be performed to measure the impact of corrective actions implemented. References and/or acknowledgements: Thanks to pharmacists and medical and paramedical staffs for their collaboration. No conflict of interest